KINERJA PENYULUH PERTANIAN DI JAWA BARAT - Nani Sufiani Suhanda; Amri Jahi; Basita Ginting Sugihen; Djoko Susanto (Jurnal Penyuluhan, 2008)
The study was conducted in August through Desember 2007. The objectives of this study were:1) to identify their job performance and 2) to determine the relationship of the agent characters and their job performances at different type of extension institution in district level. A total of 260 AEA from 17 districts in West Java were selected by stratified randomized sampling technique with proportional allocation as sample of the study. Descriptive statistics were used to determine the agents’ distribution on certain characteristics. The results shown that some substantial works need to be done in order to improve the agents’ performances due to low hygiene factors and insufficient of motivating factors. Furthermore, the Kendall coefficient of concordance W obtained mostly high and highly significant. Therefore, it were concluded respectively that AEA performed best in involving informal leaders, farmer group development, extension work plan, using extension method, program planning; and performed well in evaluation and reporting subject matters of development, farmer self reliance development, office maintenance and administrative, rural economic development and need assessment. Finally, Agriculture extension agent performed unsatisfactorily in evaluation and reporting, networking and professional development.